GENETIC TRANSFORMATION OF CERATOTHECA TRILOBA FOR THE PRODUCTION OF ANTHRAQUINONES FROM HAIRY ROOT CULTURES - Naicker, Leeann; Mohanlall, Viresh; Odhav, Bharti (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Ceratotheca triloba was found to contain three anthraquinones (9, 10-anthracenedione, 1-hydroxy-4-methylanthraquinone and 5, 8-dimethoxy-2, 3, 10, 10a-tetrahydro-1H, 4aH-phenanthrene-4, 9-dione [DTP]) in its roots. Inhibition of the human topoisomerase II enzyme is the basis of some currently used cancer drugs such as doxorubicin which is shown to be cardio-toxic. For this reason we decided to investigate anthraquinones from C. triloba as a possible anticancer drug, however the main limitation was the large quantities of roots that are required to obtain a good yield of the active compound. Therefore the aim of this research was to obtain a higher yield of anthraquinones in hairy roots cultures than the parent plant as well as to compare yields of hairy root, cell suspension and shoot cultures. Materials and Methods: Protocols for seed sterilization, seed germination, shoot cultivation, callus induction, A. rhizogenes mediatedtransformation and hormone supplementations of hairy roots were developed. Results:The results revealed that stem explants was susceptible to transformation by Agrobacterium rhizogenes at a low optical density of 0.2. Induced hairy roots were decontaminated by exposure to cefotaxime at 500mg.l-1 for five days and then 200mg.l-1 for eight days. Visualization of culture extract profiles by TLC revealed anthraquinones were present in all cultures. Analysis of the culture extracts by HPLC showed the highest yield of anthraquinones was produced in hairy root cultures supplemented with 1-Naphthaleneacetic acid [NAA] (8 mg). This was a 17 fold increase compared to field roots (0.47 mg). Conclusion:Therefore C. triloba hairy root cultures are the preferable biological system for anthraquinones production over shoot (0.13 mg) and cell suspension cultures (0.70 mg).